The Resilient Role of Generation Z in Building the Unity and Association of the Indonesian Nation Through Pancasila Education in the Era 5.0 - Azhari, Sarah; Camellia, Camellia (Universitas Negeri Surabaya, 2024)
Along with the development of today's technology, many problems arise, and as Generation Z is present simultaneously with technology in the 5.0 era must be capable​ of maintaining and internalising the values of Pancasila amidst the current speed technology. The method used for this writing is a literature study; the literature results show that significant threats are related to the shift in national identity and the weakening of Pancasila values due to the rapid development of technology. Therefore, Pancasila education is here to make Gen Z aware of constantly strengthening unity and the unity of the Indonesian nation in the 5.0 era. Gen Z plays a role in maintaining unity and integrity by preserving the moral values taught by our ancestors through social media as a platform for spreading national and cultural values, can filter divisive information in defending unity and integrity, and mobilise social action to help the community. Therefore, Gen Z can become a strong generation, with the spirit of Pancasila, and play an active role in guarding the integrity Indonesian nation.